Community Participation in the Development of "Kapalo Banda" Tirta Tourism Nagari Taram, Lima Puluh Kota, Sumatra Barat - Fauzan, Muhammad; Hendri, Ridar; Zulkarnain, Zulkarnain (Jurnal Perikanan dan Kelautan, 2025)
Community participation is an opportunity for residents to participate effectively in managing Tirta tourism. Tirta Kapalo Banda Tourism is managed by the community, which acts as tourism managers and business owners around Kapalo Banda's irrigation waters and forests in Nagari Taram. This study aims to describe the stages of participation, analyze the level of participation, and find out the supporting and inhibiting factors of community participation in the development of Tirta Kapalo Banda Tourism. The method used is descriptive research with a qualitative approach. The informants in this study were determined purposively, namely representatives of the Taram Nagari Government, tourism managers, and business owners. The data analysis used is Miles and Huberman analysis, which starts from data reduction, data presentation, and conclusion drawing. The results showed that the participation stage of the Nagari Taram community was involved in all stages, starting from the decision-making stage, the implementation stage, the benefit-taking stage, and the evaluation stage. The degree of participation of the Nagari Taram community is in the tokenism degree category. Supporting factors for community participation are motivational factors, funds and personal assets, opportunities, training, and socialization, and inhibiting factors for community participation are weather factors and natural disasters, rules for becoming tourism managers, other jobs, and negative influences from outside.